P53 gene alterations in human tumors: perspectives for cancer control - Hollstein, Monica; Soussi, T.; Thomas, G.; Brevern, Marie-Charlotte von; Bartsch, Helmut (Risk and progression factors in carcinogenesis, 1997)
Alterations of the p53 gene are found in the majority of human tumors (Caron de Fromentel and Soussi 1992; Hollstein et al. 1991; Tominaga et al. 1992; Levine et al. 1991; Greenblatt et al. 1994). The encoded nuclear phosphor protein is a transcription factor that binds to a specific DNA motif and trans activates genes controlling cell cycle checkpoints, DNA repair, and cell death (Clarke et al. 1993; Lane 1993; Lowe et al. 1993; El Deiry et al. 1994). The p53 protein can also play a role in maintaining the integrity of the genome by sensing DNA changes, by affecting DNA repair processes, and perhaps by influencing homologous recombination events or DNA replication (Kastan et al. 1992; Yin et al. 1992; Livingstone et al. 1992; Lane 1994; Cox et al. 1995; Jayaraman and Prives 1995; Wang et al. 1995).